Imposter Syndrome Among Pre-service Educators and the Importance of Emotion Regulation - LaPalme, Matthew; Luo, Peihao; Cipriano, Christina; Brackett, Marc (Frontiers in Psychology, 2022)
This study examined the prevalence and impact of imposter syndrome (IS) on a sample of pre-service educators. We report a majority of pre-service educators experience IS; 93% experience moderate levels and 54% had frequent or severe levels of imposter thoughts, and further that IS was negatively associated with educator well-being. We also investigated the effects of minority group membership on experiences of IS, and found that IS was more severe for women and queer minorities, but less severe for racial minorities. Lastly, we investigated the potential for healthy emotion regulation to mitigate the effects of IS on pre-service educator well-being and found that adaptive emotion regulation strategy use mitigates the effects of IS, which may provide a viable means for addressing this pervasive issue among educators, and specifically among those with minoritized identities. We discuss the implications of our findings for educational training and improving the experiences of pre-service educators.